Sustained brain response to repeated drug cues is associated with poor drug‐use outcomes. (26th February 2021) - Regier, Paul S.; Jagannathan, Kanchana; Franklin, Teresa R.; Wetherill, Reagan R.; Langleben, Daniel D.; Gawyrsiak, Michael; Kampman, Kyle M.; Childress, Anna Rose
Abstract: A threefold increase in fatal cocaine overdoses during the past decade highlights the critical lack of medications for cocaine use disorders. The brain response to drug cues can predict future drug use; however, results have been mixed. We present preliminary evidence that a sustained response to repeated cocaine cues within a single task is a significant predictor of drug‐use outcomes. Seventy‐three cocaine inpatients were administered a passive‐viewing fMRI task, featuring 500 ms novel evocative (cocaine, sexual, aversive) and neutral comparator cues in the first half (Half1), which were then repeated in the second half (Half2). After the baseline scan, patients received eight outpatient treatment weeks with twice‐weekly drug screens. Drug‐use outcome groups were empirically defined based on cocaine‐positive or missing urines averaged across the outpatient phase: GOOD (<40%), POOR (>85%), and Intermediate (INT, between 40% and 85%) outcomes. Differences of response to initial (Half1) and repeated (Half2) cues in a priori (cue‐reactive) regions were tested between outcome groups (3 [Group] × 2 [Halves] ANOVA). An interaction was found in the brain response to drug (but not sex or aversive) cues, with a significant difference between the GOOD and POOR outcome groups in Half2, driven by a significant decrease in brain response by the GOOD outcome group and a sustained brain response by the POOR outcome group, to repeated cocaine cues. The brain response to repeated drug cues may be a useful predictor of future drug use, encouraging future intervention studies to restore a "healthy" (decreasing) response to the repeated presentation of drug cues. Abstract : Cocaine patients with a sustained response to cocaine(‐neutral) cues across two halves of a cue reactivity task proceed to "POOR" drug‐use outcomes, while a reduction in responding is linked to "GOOD" drug‐use outcomes. Outcomes across eight outpatient weeks were classified according to average percent cocaine‐positive/missing urines: <40%, "GOOD"; >85%, "POOR"; intermediate (INT). Drug and neutral cues were "novel" in Half1 and then repeated in the Half2 of the task. #Main effect of Halves and *significant t‐tests, FDR corrected.